Perencanaa Sistem Penyediaan Air Baku di Kecamatan Punduh Pidada dan Kecamatan Padang Cermin, Kabupaten Pesawaran - Kristia, Merida; Susilo, Gatot Eko; Romdania, Yuda (Universitas Lampung, 2016)
The main needs of water for various purposes will continue to increase based on thenumber of people who continue to grow and the development of the rate of developmentsin various sectors. On the other hand, the number of infrastructure delivery of water iscurrently still relatively limited, that hasn’t meet the needs of water. The demandsunavoidable, but shall predictable and planned utilization as well as possible. A trendfrequent are the imbalance between supply and demand for water. To achieve a balancebetween the need for water and availability of water in the future , efforts are required tomeet builders infrastructure raw water community.Domestic water needs for Padang Cermin sub-district is 32,46 l / s and Punduh Pidadasub-district is 10 l / s for 2015. For the next 20 years, the demands for water will be71,18 l/s for Padang Pidada sub-district and 71,18 l/s for Padang Cermin sub-district.The availability of water must meet the size of the high demand for water in order tosatisfy their daily needs. Methods used to acknowledge the number of the availability ofwater is the method by F.J. Mock. The calculation on that available minimum dischargein das way selorejo is 78 l / s and das way curup is 97 l / s.From the calculation on above, the availability and needs water at das way curup anddas way selorejo had a surplus of the availability of water because environmentalconditions in kecamatan punduh pidada and kecamatan padang cermin is in goodcondition.Keywords : Water needs, availability of water, Water Supply Building Materials